2003
DOI: 10.1001/archpedi.157.12.1232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orange and Apple Juices on Iron Absorption in Children

Abstract: As children absorb iron well from a meal that includes either orange or apple juice, a preference for apple juice does not pose a concern with regard to the prospect of iron-deficiency anemia, which remains a significant health problem in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
(29 reference statements)
1
18
1
2
Order By: Relevance
“…The women who had fruit juice at least once a week had significantly higher SF concentration. Fruit juice is high in vitamin C, and the bioavailability of iron is enhanced by vitamin C (Shah et al 2003). On the other hand, the women who consumed brown bread regularly ($ 1 time/day) and those who had tea or coffee at least once a week had significantly lower SF concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The women who had fruit juice at least once a week had significantly higher SF concentration. Fruit juice is high in vitamin C, and the bioavailability of iron is enhanced by vitamin C (Shah et al 2003). On the other hand, the women who consumed brown bread regularly ($ 1 time/day) and those who had tea or coffee at least once a week had significantly lower SF concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the pronounced enhancing effects of added AA on the absorption of dietary NHI when foods or drinks rich in or supplemented with AA were tested [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the intake of OrAP with different concentrations prevents these pathogenic changes in the blood picture of rats. These results could be contributed to the improvement in iron absorption from rat's gut after consumption of OrAP due to its high content of ascorbic acid (41).…”
Section: Discussionmentioning
confidence: 88%